EXPLORING THE USE OF GNSS DATA IN THE IDENTIFICATION OF ACTIVITY AREAS FOR CENSUS ENUMERATION EXERCISE (FUDMA JOURNAL OF SCIENCES, 2023)
The Global Navigational satellite System (GNSS) is a satellite based positioning tool that uses signals from artificial satellites in the space to determine time, velocity and positions. The GNSS receiver has countless uses and these may include navigation, surveying and Mapping in general. The aim of this study is to determine, using the GNSS, areas with dense population and more so, areas of much activities for census planning exercise. The Hi-Target V30 GNSS receiver and its accessories were used for the study. The Hi-Target V30 Standalone Receiver’s Data were collected for 12 months interval observation. Observations were carried out for 1 hour each on ten (10) different stations and the GNSS raw data were downloaded and converted into RINEX data. A Post-Processing platform was used to process the result in ITRF 14 and WGS 84 datum. The differencing of results showed shifts in the directions to much denser populations areas. These shifts, after interpretations could assist enumerators in further decision making.  It is obvious that, the GNSS potentials are limitless as the aim of the research was achieved.
Keywords: GNSS Receiver; coordinate; RINEX data; datum; ITRF 14